Addition of fructose to a carbohydrate-rich breakfast improves cycling endurance capacity in trained cyclists - Podlogar, T.; Cirnski, S.; Bokal, S.; Verdel, N.; Gonzalez, J. T. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
It was previously demonstrated that postexercise ingestion of fructose-glucose mixtures can lead to superior liver and equal muscleglycogen synthesis as compared with glucose-based carbohydrates (CHOs) only. After an overnight fast, liver glycogen stores are reduced, and based on this we hypothesized that addition of fructose to a glucose-based breakfast would lead to improved subsequent endurance exercise capacity. In this double-blind cross-over randomized study (eight males, peak oxygen uptake: 62.2 ± 5.4 ml·kg-1·min-1), participants completed two experimental trials consisting of two exercise bouts. In the afternoon of Day 1, they completed a cycling interval training session to normalize glycogen stores after which a standardized high-CHO diet was provided for 4 hr. On Day 2, in the morning, participants received 2 g/kg of CHOs in the form of glucose and rice or fructose and rice, both in a CHO ratio of 1:2. Two hours later they commenced cycling exercise session at the intensity of the first ventilatory threshold until task failure. Exercise capacity was higher in fructose and rice (137.0 ± 22.7 min) as compared with glucose and rice (130.06 ± 19.87 min; p = .046). Blood glucose and blood lactate did not differ between the trials (p > .05) and neither did CHO and fat oxidation rates (p > .05). However, due to the duration of exercise, total CHO oxidation was higher in fructose and rice (326 ± 60 g vs. 298 ± 61 g, p = .009). Present data demonstrate that addition of fructose to a glucose-based CHO source at breakfast improves endurance exercise capacity. Further studies are required to determine the mechanisms and optimal dose and ratio.